2016
DOI: 10.1177/1078155216660185
|View full text |Cite
|
Sign up to set email alerts
|

Severe phototoxic reaction secondary to subcutaneous 5-azacitidine

Abstract: Phototoxicity occurs when the effects of sunlight and certain drugs converge at the skin level. Various pharmacologic agents have been linked to photosensitivity, including agents used in hematology and oncology. We describe herein a severe phototoxic response to subcutaneous 5-azacitidine. There are no previous reports of phototoxicity reactions to this agent in the published literature. As 5-azacitidine is frequently used to treat patients with myelodysplastic syndromes and acute myeloblastic leukemia, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…As DNMT inhibitors were usually used for cancer treatment but not for FSs, which might have unpredictable side effects on infants, we aimed to search an effective and harmless treatment that could also rescue the future memory deficits induced by prolonged FSs. Here, we investigated the effect of an enriched environment (EE) protocol during weaning period on adult memory performance.…”
Section: Resultsmentioning
confidence: 99%
“…As DNMT inhibitors were usually used for cancer treatment but not for FSs, which might have unpredictable side effects on infants, we aimed to search an effective and harmless treatment that could also rescue the future memory deficits induced by prolonged FSs. Here, we investigated the effect of an enriched environment (EE) protocol during weaning period on adult memory performance.…”
Section: Resultsmentioning
confidence: 99%
“…Other than localized reactions at the injection site, few generalized reactions are reported in the literature. Keating et al reported a severe phototoxic reaction due to subcutaneous 5-azacitidine [6]. A case series of azacitidine-associated generalized urticarial skin rash has been reported in the literature, which resolved effectively after the use of concomitant low-dose oral steroids [7].…”
Section: Discussionmentioning
confidence: 99%
“…5-azacitidine also causes phototoxicity. Clinical manifestations are pruritic, serpiginous, tender lesions [ 227 ].…”
Section: Characteristics Of Drugs With Photosensitive Potentialmentioning
confidence: 99%